1995
DOI: 10.1016/0014-5793(95)00811-m
|View full text |Cite
|
Sign up to set email alerts
|

Proposed cation‐π mediated binding by factor Xa: a novel enzymatic mechanism for molecular recognition

Abstract: Factor Xa (FXa) is an important serine protease in the blood coagulation cascade. Small synthetic competitive inhibitors of FXa are under development as potential anticoagulants. To better understand FXa structural features and molecular recognition mechanisms, we have constructed three dimensional models of FXa-inhibitor complex structures via a new search approach that samples conformational space and binding space simultaneously for DABE and DX-9065a, two bis amidinoaryl derivatives that are among the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 37 publications
2
35
0
Order By: Relevance
“…(ii) the overall inhibitor conformation proposed by Lin and Johnson [13] is much closer to that which we see. Due to a slight inclination of the napthalene group, however, the pyrrolidinyl group does not extend as far along the enzyme surface.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…(ii) the overall inhibitor conformation proposed by Lin and Johnson [13] is much closer to that which we see. Due to a slight inclination of the napthalene group, however, the pyrrolidinyl group does not extend as far along the enzyme surface.…”
Section: Discussionsupporting
confidence: 81%
“…Structure-activity relationships for DX9065a have shown that the distal basic moiety plays a major role in the inhibition of factor Xa, whilst the propionic acid group is responsible for its lack of activity against thrombin [10]. Molecular modelling has attributed the basicity requirement variously to interaction with factor Xa Glu-97 [10], the carbonyl group of Glu-97 [12] or to a novel cationqr interaction with the aromatic rings of Trp-215, Tyr-99 and Phe-174 [13]. Modelling studies have further proposed that selectivity against thrombin is due to electrostatic repulsion between the side chain of thrombin in factor Xa) and the propionic moiety [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We present here the crystal structure of the factor Xa⅐DX-9065a complex. The inhibitor binds in the active site in an extended conformation, which was expected from earlier studies (14,15). Both hydrophobic and electrostatic interactions characterize the complex formation, which is also accompanied by local rearrangements in the active site of fXa.…”
mentioning
confidence: 53%
“…Cation-IT interactions have been considered in such diverse systems as acetylcholine receptors (nicotinic, muscarinic, and ACh esterase), K+ channels, the cyclase enzymes of steroid biosynthesis, and enzymes that catalyze methylation reactions involving S-adenosylmethionine (1). Cation-Ir interactions have also been invoked to rationalize specific drug-receptor interactions (8)(9)(10)(11) …”
Section: Introductionmentioning
confidence: 99%